VISI DRAMATIK SOEKARNO DALAM DRAMA RAINBOW: POETRI KENTJANA BOELAN - Ikhsan Satria Irianto (Pascasarjana Institut Seni Indonesia Padang Panjang, 2021)
This research aims to uncover the vision behind the writing and performance of the drama Rainbow: Poetri Kentjana Boelan. The case in question in this research is how is Soekarno's dramatic vision in the drama Rainbow: Poetri Kentjana Boelan? This study uses a theater history study approach with qualitative research methods. The theoretical framework chosen to answer the research questions is the concept of dramatic vision. Some of the conclusions generated from this research are through the drama Rainbow: Poetri Kentjana Boelan, Soekarno provides education and raises awareness and establishes communication and designs struggles to realize Indonesian independence.Keywords: Soekarno, Rainbow: Poetri Kentjana Boelan, Dramatic VisionAbstrakPenelitian ini bertujuan untuk mengungkap visi yang melatarbelakangi penulisan dan pementasan drama Rainbow: Poetri Kentjana Boelan. Kasus yang dipertanyakan dalam penelitian ini adalah bagaimana visi dramatik Soekarno dalam drama Rainbow: Poetri Kentjana Boelan? Penelitian ini menggunakan pendekatan kajian sejarah teater dengan metode penelitian kualitatif. Kerangka teoritis yang dipilih untuk menjawab pertanyaan penelitian adalah konsep visi dramatik. Beberapa kesimpulan yang dihasilkan dari penelitian ini adalah melalui drama Rainbow: Poetri Kentjana Boelan, Soekarno memberikan edukasi dan menumbuhkan kesadaran serta menjalin komunikasi dan merancang perjuangan untuk mewujudkan kemerdekaan IndonesiaKata Kunci: Soekarno, Rainbow: Poetri Kentjana Boelan, Visi Dramatik